Variability of behavioural responses to transcranial magnetic stimulation: Origins and predictors. (July 2015) - Nicolo, Pierre; Ptak, Radek; Guggisberg, Adrian G.
Abstract: Transcranial magnetic stimulation (TMS) may modulate the excitability of local cortical stimulation sites and distant functionally interconnected regions for minutes, hours or even days. The effects of TMS suggest that it not only acts on activity of the stimulated area, but also on its connections with remote areas. Due to these properties one of the main rationales for the application of TMS in stroke patients is to improve imbalance in interhemispheric inhibition. However, given that TMS may have excitatory or inhibitory effects the impact of stimulation is not easy to predict. In this review, we discuss the different factors that determine the magnitude and quality of physiological and behavioural responses to TMS. Whether TMS is mainly excitatory or inhibitory not only depends on the parameters of stimulation such as pulse frequency and duration, but also on baseline activity of neural tissue before stimulation, or even on cognitive factors such as attention. A major challenge for the application of TMS as therapy method is to identify predictors of positive effects in individual patients. Neuroimaging studies measuring hemodynamic or electrophysiological responses show that changes in interhemispheric competition or adaptations of functional networks in patients with focal brain lesions may predict the individual response to brain stimulation. Such techniques have the potential to select the most appropriate among different intervention methods for an individual patient. Highlights: Transcranial magnetic stimulation (TMS) may have excitatory or inhibitory effects. TMS effects depend on stimulation parameters and physiological factors. Predicting responses to TMS is essential for the programming of interventions. Imaging of network activity may help to predict individual responses to stimulation.